Uso de extratos vegetais para o controle de fungos em sementes crioulas - Lima, Juliana Trindade (2023)
Creole seeds can be defined as those traditional varieties of plants cultivated and adapted to the places where they have developed for many years. They constitute an important way of recovering and preserving the genetic base of many species of cultivated plants. Precarious storage conditions in agroecological crops can contribute to the occurrence of several fungi that infest native seeds. These organisms are able to promote faster deterioration of harvested seeds and affect their germination, so farmers resort to improved seeds and/or seeds treated with chemical fungicides, putting the survival of this genetic heritage stored in vivo at risk. Extensive and repeated application of these synthetic agrochemicals can lead to negative effects such as resistant fungi, environmental and non-target organism contamination. Therefore, they create an impetus for the search for alternative control measures that are naturally safe, such as plant extracts with antifungal potential. Aroeira extracts (Schinus terebinthifolia Raddi) and clove basil (Ocimum gratissimum L.) have demonstrated an inhibitory effect on the growth of post-harvest fungi. Thus, the objective was to evaluate the effects of plant extracts on fungal control and on the physiological quality of native bean and corn seeds before and after storage. Mastic and clove basil leaves were collected at the Reginaldo Conde Agricultural Engineer Experimental Farm (FERC) at the Capixaba Institute for Research, Technical Assistance and Rural Extension (INCAPER), Viana, ES. The ethanolic extracts were obtained by maceration in ethanol and subsequent fractionation with solvents of increasing polarity (hexane, dichloromethane, ethyl acetate and butanol). Ethanol extracts and their respective fractions of increasing polarity of leaves of both plants were investigated for chemical composition, in vitro antioxidant and antifungal activity on fungi associated with creole seeds during storage. The ethanolic extract and the dichloromethane fraction of both plants showed the best results for inhibiting the in vitro fungal growth of Aspergillus sp. and Rhizopus sp. The butanol fraction of aroeira showed the highest antioxidant capacity, as in clove basil the ethanolic extract had this effect more pronounced. In view of the antifungal results, clove clove extracts were more active against the fungi tested. Seeds were purchased from the Instituto Federal of Espírito Santo seed bank, campus Santa Teresa, ES. The seeds were submitted to ethanolic extract and dichloromethane fraction of clove basil leaves and eugenol nanoemulsion and stored in plastic containers at room temperature. The sanity and germination test of the seeds was carried out, in the pre and post storage. The fungi found in the seeds are of the genera Aspergillus, Penicillium and Rhizopus. In bean seeds, treatment with eugenol nanoemulsion was more effective in reducing the incidence of pathogens, on the other hand, in corn seeds, ethanolic extract and dichloromethane fraction were more active. The dichloromethane fraction and the eugenol nanoemulsion negatively affected the seed vigor of both crops. The results indicate potential use of O. gratissimum extracts in the preservation of stored seeds.